Chemical structure and antiviral activity of carrageenans from Meristiella gelidium against herpes simplex and dengue virus - De S.F. Tischer, Paula Cristina (2006)
Chemical and spectroscopic methods showed that the major KCl-precipitated galactans from Meristiella gelidium (Solieriaceae) are iota/kappa/nu-hybrid carrageenans with the former one in higher proportion. These carrageenans showed, by HPSEC-MALLS analysis, unimodal symmetrical peaks with MW of 425.6–956.7 kDa. The effectiveness of the crude extracts from M. gelidium against HSV-2 was higher than the corresponding extract from G. griffithsiae, previously determined. However, when considering the homogeneous carrageenans, the fractions obtained from both seaweeds showed the same level of activity. The extracts and carrageenan derived from M. gelidium were more effective inhibitors of DENV-2 if compared with G. griffithsiae samples and reference polysaccharides. The most active fraction obtained from M. gelidium showed a selectivity index against HSV-2 of 25,000, a value high enough to consider this carrageenan as a promising agent to be evaluated for the treatment of genital HSV-2 infections.